2009
DOI: 10.14411/eje.2009.067
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature on the reproduction and development of Trichogramma buesi (Hymenoptera: Trichogrammatidae)

Abstract: Abstract. At emergence females of Trichogramma had a lot of mature eggs in their ovaries, but some delayed parasitization or refused to parasitize a laboratory host. The effect of constant and alternating temperatures on the percentage of Trichogramma buesi females parasitizing Sitotroga cerealella eggs and the duration of the pre-parasitization period were investigated. The temperature dependencies of the rate of preimaginal development, pre-emergence survival, number of eggs laid daily, and total lifetime fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 50 publications
1
9
0
6
Order By: Relevance
“…These results are in accordance with other studies showing that T. evanescens laid more eggs in the first 24 h (Achiri et al 2020). It is known that the mean number of eggs laid per female generally decreases over time or with the age of the parasitoid (Reznik et al 2009). Trichogramma chilonis Ishii on eggs of C. cephalonica and T. cacoeciae on Cydia pomonella (Linnaeus, 1758) (Lepidoptera: Tortricidae) eggs showed a systematic decrease in the numbers of eggs laid per female over time (Mansour 2019).…”
Section: Effect Of Different Ephestia Kuehniella Diets On the Reprodusupporting
confidence: 93%
“…These results are in accordance with other studies showing that T. evanescens laid more eggs in the first 24 h (Achiri et al 2020). It is known that the mean number of eggs laid per female generally decreases over time or with the age of the parasitoid (Reznik et al 2009). Trichogramma chilonis Ishii on eggs of C. cephalonica and T. cacoeciae on Cydia pomonella (Linnaeus, 1758) (Lepidoptera: Tortricidae) eggs showed a systematic decrease in the numbers of eggs laid per female over time (Mansour 2019).…”
Section: Effect Of Different Ephestia Kuehniella Diets On the Reprodusupporting
confidence: 93%
“…In our experiments, parasitism rate was affected by temperature for each all four Trichogramma species, though all females did parasitize at least one egg under all temperature regiments tested (which is not always the case, see Reznik et al 2009). The variation in parasitism rate may be the result of local adaptation to the various climatic conditions where each species was collected.…”
Section: Discussionmentioning
confidence: 64%
“…Other potential factors include higher host numbers or species (Wiedenfeld et al ) or host phenotypes and genotypes that sustain much higher infestation intensities. In addition average temperatures are lower at higher altitudes, which is known to affect P. downsi development and infestation intensity negatively (Mosquera ), as also shown for other insects (Taylor , Ratte , Reznik et al ). A recent study in Santa Cruz found low P. downsi activity, as shown by low numbers in fly traps when temperatures were below ~19–21°C (Causton et al ).…”
Section: Discussionmentioning
confidence: 75%